Genetic predisposition for tympanosclerotic degeneration - (:unkn) unknown (SPRINGER, 2002)
Atherosclerosis and tympanosclerosis are disorders that affect different organs in the body. When tissue samples taken from atherosclerotic and tympanosclerotic lesions are compared under light and electron microscopes, common pathological characteristics become apparent in both tissues. These similarities indicate that genetic predisposition to atherosclerosis is also seen in the middle ear. For the purpose of evaluating this genetic predisposition, the incidence of tympanosclerosis in atherosclerotic patients was examined and compared with the normal population. Otoscopic examination of 1,024 atherosclerotic patients was performed, and myringosclerosis was revealed in 66.6%. Myringosclerosis was found in 36 out of 300 non-atherosclerotic patients (12%). In the group of atherosclerotic patients, 174 individuals had past histories of previous car infections. Myringosclerosis was detected in 147 of these patients (84.5%) during ear examinations. In 637 non-atherosclerotic patients with histories of ear infections, this figure was 114 (17.7%). The high rate of tympanosclerosis observed in atherosclerotic patients in comparison to the normal population was found to be statistically significant. These findings indicate that there must be a genetic predisposition for sclerotic degeneration in some individuals.
Keywords: tympanosclerosis; atherosclerosis; genetic predisposition; ATHEROSCLEROSIS; PATHOGENESIS; INSERTION; CHILDREN; SEX